Changes in Glycolytic Pathway in SARS-COV 2 Infection and Their Importance in Understanding the Severity of COVID-19 - Santos, Adalberto (2021)
COVID-19 is an infectious disease caused by Coronavirus 2 (SARS-CoV-2) that may lead to a severe acute respiratory syndrome. Such syndrome is thought to be related, at least in part, to a dysregulation of the immune system which involves three main components: hyperactivity of the innate immune system; decreased production of type 1 Interferons (IFN) by SARS-CoV-2-infected cells, namely respiratory epithelial cells and macrophages; and decreased numbers of both CD4+ and particularly CD8+ T cells. Herein, we describe how excessive activation of the innate immune system and the need for viral replication in several cells of the infected organism promote significant alterations in cells’ energy metabolism (glucose metabolism), which may underlie the poor prognosis of the disease in severe situations. When activated, cells of the innate immune system reprogram their metabolism, and increase glucose uptake to ensure secretion of proinflammatory cytokines. Changes in glucose metabolism are also observed in pulmonary epithelial cells, contributing to dysregulation of cytokine synthesis and inflammation of the pulmonary epithelium. Controlling hyperglycolysis in critically ill patients may help to reduce the exaggerated production of pro-inflammatory cytokines and optimise the actions of the adaptive immune system. In this review, we suggest that the administration of non-toxic concentrations of 2-deoxy-D-glucose, the use of GLUT 1 inhibitors, of antioxidants such as vitamin C in high doses, as well as the administration of N-acetylcysteine in high doses, may be useful complementary therapeutic strategies for these patients, as suggested by some clinical trials and/ or reports. Overall, understanding changes in the glycolytic pathway associated with COVID-19 infection can help to find new forms of treatment for this disease.